How boards influence business performance: developing an explanation. Issue 8 (7th November 2016) - Crow, Peter R.; Lockhart, James C.
Abstract : Purpose: The purpose of this paper is to explore the relationship between boards and board activity and subsequent business performance, in the context of high-growth companies, through the lens of decision making and business performance. Design/methodology/approach: A critical realist approach was used to conduct a longitudinal multiple-case study of two medium-sized, quasi-public high-growth companies. Data collection included first-hand observations of boards in session, semi-structured interviews with key actors and the inspection of board and company documentation. An iterative approach to analysis was used to gain an in-depth understanding of how the boards worked and how they sought to exert influence. Findings: The paper provides empirical insight about board involvement in strategic management. A proactive involvement by boards in the strategy development process and assessment of strategic options, and a collaborative form of board involvement in strategic management together with management is indicated as being important if the board is to exert influence beyond the boardroom. A conceptual model of a collaborative form of board-management interaction is developed. Practical implications: The paper provides guidance for boards, suggesting that a more direct level of involvement in strategic management by the board together with management may be material to improved business performance. Originality/value: The paper responds to calls for more research on the relationship between boards and business performance. It contributes much-needed first-hand evidence from within the boardroom.